Targeting of putative fimbrial gene for detection of S. Typhi in typhoid fever and chronic typhoid carriers by nested PCR - Pratap, Chandra Bhan; Kumar, Gopal; Patel, Saurabh Kumar; Verma, Ajay Kumar; Shukla, Vijay K; Kumar, Kailash; Nath, Gopal (The Journal of Infection in Developing Countries, 2013)
Introduction: It is important to identify Salmonella Typhi infection quickly to treat acute fever patients and to prevent transmission by chronic typhoid carriers; therefore, a very specific and sensitive diagnostic technique is highly desirable, especially in endemic areas. The objective of this study was to develop a PCR protocol targeting the putative fimbrial staA gene of S. Typhi. This is a preferred target gene that is specifically amplified in the S. Typhi serotype compared to the commonly targeted fliC gene which may also be amplified from the non-typhoidal Salmonella Munchen serotype. Methodology: A new nested PCR primer methodology was designed to target the staA gene, which is a member of the fimbrial gene family specific to Salmonella Typhi only. Results: The primers were found to be very specific as the desired amplicon (377 bp) could be generated exclusively from S. Typhi strains including the reference strain (MTCC 3216) and 78 clinical isolates . Restriction digestion with HinfI confirmed the identity of the amplified DNA fragment in clinical specimens of S. Typhi origin. Furthermore, these primers were able to detect a minimum of three colony forming units per ml (1fg) in spiked blood samples. The detection sensitivity of the described primers is comparable to that of previously published primers targeting fliC gene sequences. Conclusions: This study indicates that the primers targeting the putative fimbrial staA gene are very specific to the Typhi serotype and may be a better alternative to fliC targeted amplification based diagnosis.